Software verification and validation with destiny a parallel approach to automated theorem proving. - Dykstra, Josiah (Crossroads : the ACM student magazine.)
This paper presents an introduction to computer-aided theorem proving and a new approach using parallel processing to increase power and speed of this computation. Automated theorem provers, along with human interpretation, have been shown to be powerful tools in verifying and validating computer software. Destiny is a new tool that provides even greater and more powerful analysis enabling greater ties between software programs and their specifications.